SUNSET YELLOW DYE ADSORPTION FROM AQUEOUS SOLUTIONS USING ACTIVATED CARBONS DERIVED FROM AGRICULTURAL WASTE - Ensuncho, Adolfo E. (2015)
In this work was studied the adsorption of sunset yellow dye with different type of activatedcarbon obtained from vegetable waste. The carbons were characterized by infraredspectroscopy, X-ray diffraction and electron microscopy, obtaining typical results forcarbonaceous materials. Surface areas of activated carbon were determined by nitrogenisotherms. Similarly, dye removal isotherms were evaluated taking into account, contact timeeffect, pH, initial concentration and amount of adsorbent. Corn cob carbons, showed highestremoval percentage with respect at the carbons of coconut husks and rice husks. Langmuir’sisotherm model is adjusted more appropriately to these results. We found that, pseudo secondorder kinetics model describes in good agreement the adsorption of sunset yellow dye withactivated carbons.